THE INFLUENCE OF STORY MAPPING STRATEGY AND READING MOTIVATION TOWARDS READING COMPREHENSION ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS AT JUNIOR HIGH SCHOOL 3 OF SUNGAI LILIN - Apriyanti Nababan; Tahrun Tahrun; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2020)
This research aims to analyze the Influence of Story Mapping strategy and reading motivation towards reading comprehension achievement. The writer distributed pretest, posttest, and questionnaire in collecting the data.  Then in analyzing the data, the writer used a t-test and two-way ANOVA. The findings of this study were (1) There was a significant influence of the Story Mapping strategy towards the scores of reading comprehension achievement on the narrative text. (2) There was not any significant influence of the Story Mapping strategy towards the scores of reading comprehension achievement on the narrative text. (3) There was a significant influence of the conventional technique towards the scores of reading comprehension achievement on the narrative text. (4) There was not any significant influence of the conventional technique towards the scores of reading comprehension achievement on the narrative text. (5) There was a significant interaction effect of the Story Mapping strategy and reading motivation on the eighth students’ reading comprehension achievement on the narrative text.